USP35 promotes the growth of ER positive breast cancer by inhibiting ferroptosis via BRD4-SLC7A11 axis - Jiawei Cao; Tao Wu; Tong Zhou; Zewei Jiang; Yinrui Ren; Jiawei Yu; Jiayi Wang; Changrui Qian; Guang Wu; Licai He; Hongzhi Li; Rixu Lin; et al. (Communications Biology)
Abstract Anti-estrogen endocrine therapies greatly improve survival of estrogen receptor positive (ER + ) breast cancer. Unfortunately, about 30% of patients do not respond to endocrine therapies initially. We previously showed that deubiquitinase USP35 and ERα act in a positive feedback loop to promote the carcinogenesis of ER+ breast cancer although it is unclear whether USP35 regulates cell death in ER+ breast cancer. In this study, we uncovered that USP35 inhibited ferroptosis of ER+ breast cancer cells. Mechanistically, USP35 interacted with, deubiquitinated, and stabilized BRD4. Consequentially, BRD4 mediated USP35-induced SLC7A11 upregulation, inhibiting ferroptosis and promoting the growth of ER+ breast cancer cells. Furthermore, BRD4 inhibitor (+)-JQ-1 inhibited USP35-enhanced tumorigenesis in vivo. Our findings demonstrated that the USP35-BRD4-SLC7A11 axis contributes to the growth of ER+ breast cancer by inhibiting ferroptosis. Targeting USP35 together with ferroptosis inducer may represent a potential promising strategy for treating ER+ breast cancer that does not respond to endocrine therapies.